2018
DOI: 10.1136/tobaccocontrol-2017-054154
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two cities: exploring the retail impact of flavoured tobacco restrictions in the twin cities of Minneapolis and Saint Paul, Minnesota

Abstract: Policies that restrict the sale of flavoured tobacco to adult-only tobacco shops are associated with decreased availability of flavoured tobacco in convenience and grocery stores and increased proportion of tobacco inventory that is unflavoured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 10 publications
4
33
0
Order By: Relevance
“…These results are consistent with findings from recent studies evaluating the impact of similar flavoured product restriction policies implemented in NYC and two cities in Minnesota 10 11. A notable strength of the present study is that it expands on sampling used in these studies to include a state-wide sample of retailers of all types and sizes, which for Q1–Q4 comprises a full sample of all retailers in the study communities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with findings from recent studies evaluating the impact of similar flavoured product restriction policies implemented in NYC and two cities in Minnesota 10 11. A notable strength of the present study is that it expands on sampling used in these studies to include a state-wide sample of retailers of all types and sizes, which for Q1–Q4 comprises a full sample of all retailers in the study communities.…”
Section: Discussionsupporting
confidence: 88%
“…As of December 2018, 138 municipalities in Massachusetts, including Boston, have passed a flavoured restriction policy, covering 61% of the state’s total population 8. Policy evaluation studies conducted in NYC and in Minneapolis and St. Paul have shown reductions in sales of non-cigarette flavoured tobacco products in large retailers, pharmacies, grocery and convenience stores following policy implementation 9–11. However, it is not yet known whether these results extend to other localities or all types of retailers.…”
Section: Introductionmentioning
confidence: 99%
“…Of the nine excluded studies, one study found that adolescents had a 37% lower odds of ever trying flavored tobacco products and a 28% lower odds of ever using tobacco products post ban [54], two studies found that sales of other tobacco products fell [55,56], and six considered compliance [57][58][59][60][61][62]. The studies of compliance indicated mixed levels of compliance, with flavor products still available in up to 50% of retailers that were not allowed to sell flavored tobacco and smaller stores often continuing to carry banned products with staff oblivious to the ban [58,[60][61][62]. However, compliance was found to increase over time following the ban [60] and was higher in areas where investments are made in the education of store owners and staff and when there was increased enforcement [59].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work examining the impact of the 2015 Minneapolis and St. Paul flavoured (exempting menthol) restrictions found similar rates of compliance within 9 months of policy implementation. 15 In these cities, it is plausible that educational and enforcement activities by advocates and city officials associated with the 2015 flavoured restrictions, and ahead of the menthol tobacco sales copyright. Original research restriction implementation date, prepared retailers to adhere to the menthol tobacco sales restriction and resulted in relatively high rates of compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evaluations of non-menthol flavoured tobacco sales restrictions have found that these types of policies can be effective in reducing the availability of flavoured tobacco products. [15][16][17] However, because menthol has often been excluded from sales restrictions, there is a paucity of published literature about the impact of menthol tobacco sales restrictions on the retail environment. We are only aware of one published study to date that examined the impact of a menthol tobacco restriction on the retail environment.…”
Section: Introductionmentioning
confidence: 99%